Chemical characterization of Rosa damascena Miller var. trigintipetala Dieck essential oil and its in vitro genotoxic and cytotoxic properties. Issue 2 (3rd March 2016) - Abdel-Hameed, El-Sayed S.; Bazaid, Salih A.; Hagag, Heba A.
Abstract: Rosa damascena Miller var. trigintipetala Dieck (Taif rose) is considered as one of the most important economic products of Taif governorate, KSA. In this study, the different components of Taif rose essential oil were characterized using GC-MS technique. In addition, the in vitro cytotoxic, genotoxic and anticancer effects of the oil were investigated toward normal human peripheral blood lymphocytes and two kinds of human cancer cell lines; HepG2 and MCF7. GC-MS analysis showed that the acyclic monoterpene alcohols had the highest content (254.7 mg/g oil). The major components of the oil that have relative percentage > 5% were β-citronellol, geraniol, nerol, linalool, phenylethyl alcohol and nonadecane. The results showed that the oil was safe at a dose < 50 μg/mL when applied to normal human blood lymphocytes monitored by 7-AAD assay and DNA index determination. The oil exerted anticancer activity against HepG2 and MCF7 with IC50 = 13.03 ± 0.8 and 16.44 ± 1.4 μg/mL respectively. In conclusion, the essential oil of Taif rose can be used as an effective therapeutic natural agent after more toxicological in vitro and in vivo studies.